SWOT analysis of producing naked oat in northern growing conditions - Peltonen-Sainio, Pirjo; Kirkkari, Anna-Maija (MTT, 2004)
Naked oat is an under-utilised crop, which contributes less than 0.1% to the total oat acreage in Finland. Such low area under naked oat compared to conventional indicates, however, the potential for more comprehensive production. Limited interest in growing naked oat more extensively is attributed to its weaknesses, which ironically result from nakedness that is the factor making naked oat also an exceptionally attractive crop. To be able to weight the potentiality of naked oat, an analysis of weaknesses, strengths, opportunities and threats (SWOT) was carried (Peltonen-Sainio et al. 2004). Based on the relevant literature and our own experiences in growing and handling naked oat we ended up in the following results of SWOT-analysis: Strengths are 1) experience and long traditions in cultivating oat in Finland, 2) adaptation to northern growing conditions, 3) crop management comparable to that in conventional oat, 4) exceptionally high quality grain and 5) storability; Weaknesses are 1) need for compensating the reduced seed vigour by using 10 % higher seeding rate, 2) sensitivity to grain damage caused by mechanical stress and 3) incomplete expression of nakedness; Opportunities are 1) potential substitute for imported energy, 2) potential for specific, high value applications, 3) potential for future breeding success and 4) lack of economic losses related to hulls; Threats are 1) problems in availability regarding modern cultivars for farmers and lot quantities for industry, 2) lack of signs of increasing production intensity and 3) problems in producing high germination seed in northern growing conditions. After weighting all these SWOT-factors thoroughly, we ended up in concluding that naked oat is particularly attractive as on-farm feed in Finland. Peltonen-Sainio, P. et al. 2004. Agricultural and Food Science 13: in press.
Keywords: Ka; kaura; jalostus; viljely; rehu; elintarvike; jyvä; jyväydin; kuori; puinti; laatu; varastointi; sato; paljasjyväinen kaura; kuoreton kaura; grain damage; feed; naked oat; opportunities; quality; strengths; SWOT; threats; weaknesses